The Significance of Timurid Thinkers’ Views on the Upbringing of the Perfect Person in Today’s Importance - Boltaboyev Tursunaliyevich (Penerbit Jurnal Indonesia, 2024)
The article examines the development of Sufism during the Timurid period and the theoretical-methodological issues in its study, the interpretation of the concept of the perfect person in the Sufi philosophical views of the Timurids, and the relevance of the views of Timurid thinkers on the upbringing of the perfect person in today’s context. Additionally, the article analyzes the significance of the views of the Timurids’ thinkers on the upbringing of the perfect person in contemporary society.